Climate Interactions and Respiratory Diseases in Children - Ramalho, Margarida (2022)
Introduction: Temperature and relative humidity affect health, particularly the respiratory system. Children represent a risk group, due to immature systems and continual development. The present study aimed to analyze the effects of temperature and relative humidity on hospitalizations of children due to asthma exacerbations and respiratory infections. Methods: This retrospective study analyzed administrative data from patients with respiratory infections and/or asthma exacerbations who were admitted to the pediatric service in a central hospital from 2018 to 2020. Pearson and Spearman correlations, Student t test, analysis of variance, and the equivalent non-parametric tests were used to describe the association between environmental factors, such as temperature and relative humidity, on children hospitalizations due to asthma exacerbations and acute respiratory infections. Negative binomial regression was used to model the daily expected hospitalizations. Results: This study was conducted on a total of 369 clinical records of primary and secondary discharge diagnoses related to 338 children. In 2020, there was a decline in admissions, due to the COVID-19 pandemic. The viral lower respiratory infections, asthma, upper respiratory infections, and non-viral lower respiratory infections accounted for 51.2%, 17.9%, 16.3%, and 14.6% of recorded diagnoses, respectively. The mean ± standard deviation of daily temperature and relative humidity was 14.8ºC ± 4.0ºC and 77.7% ± 12.7%, respectively. A negative correlation was found with maximum temperature (p = 0.012), and a positive correlation was observed with mean relative humidity (p = 0.045). There was a significant association between viral lower respiratory infections and hospitalizations, which increased with the mean temperatures < 10.0ºC and relative humidity > 86.67%. Finally, our best model showed a negative correlation between daily mean temperature and hospitalizations (incidence rate ratio = 0.989). Conclusion: Cold and humidity were associated with hospitalizations for asthma and respiratory infections. Further studies with other variables (eg pollutants) may identify other factors more precisely and advocate prevention and health planning.